PENGARUH KOMISARIS INDEPENDEN, REPUTASI KAP, PERSISTENSI LABA, DAN STRUKTUR MODAL TERHADAP KUALITAS LABA (STUDI PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013) - Marisatusholekha Marisatusholekha; Eddy Budiono (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
This reseacrh aims to know the influence of independent board of commisioner, CPA firm’s reputation, earnings persistence, and capital structure on earnings quality. This research is classified as descriptive verificative causality research. The population of this research is all telecommunication sub-sector companies listed on the Indonesia Stock Exchange in 2009 to 2013. Employing purposive sampling technique with specific criteria, this study uses four telecommunication companies. Data is analyzed using multiple regression analysis. Independent board of commissioner, earnings persistence, capital structure, and earnings quality are measured by ratio scale. CPA firm’s reputation is measured and by using nominal scale and converted into dummy variable. Earnings quality is mesured by earnings response coefficient. The result of this research is that, either simultaniously or partially, all independent variables have no significant influence on the earnings quality.